Analysing nexus between stock market and key macroeconomic variables using cointegration and causality approaches. (17th September 2021) - Goel, Himanshu; Singh, Narinder Pal
This paper aims to analyse the nexus between Bombay Stock Exchange (BSE) and macroeconomic factors. An empirical investigation has been conducted to determine the cointegration and causality between the macroeconomic variables and the Sensex using Johansen's cointegration and Granger causality techniques. Monthly data points spanning a period of the last eight years starting from 2012 to 2019 has been used for empirical investigation. Empirical results of the cointegration technique reveal no cointegrating equations between the macroeconomic variables and the Sensex. The results of Granger causality reveal that only consumer price index Granger causes Sensex. Furthermore, the results of the regression model reveal rupee-US foreign exchange rate and Morgan Stanley Capital International world index to be significant. Also, the results show the absence of autocorrelation and multicollinearity in the dataset. The results of this paper can be of immense use for retail investors, portfolio managers, and policymakers.